NUTRITIONAL CONTENT OF CASSAVA OUTBOW IN FERMENTATION USING EM-4 AND MA-11 BIOACTIVATORS - Sirajudin, Alfian Dhonan; Sukaryani, Sri (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
This study aimed to determine the effect of the use of EM-4 and MA-11 bioactivators on the nutritional content of fermented cassava cobs. The experiment was conducted in December 2025 at the FP Laboratory of Bantara University, using an experimental approach with a completely randomized design (CRD) featuring a one-way arrangement, which included three treatments and eight replications. The treatments applied were P0: cassava cobs combined with 5 cc molasses; P1: cassava cobs mixed with 5 cc molasses and 2% EM-4; and P2: cassava cobs plus 5 cc molasses and 2% MA-11. Each sample underwent an incubation period of 7 days. The variables monitored included the levels of Dry Matter, Crude Protein, and Crude Fiber. Data were evaluated through analysis of variance (ANOVA) followed by Duncan's Multiple Range Test. The results showed that the application of bioactivators significantly affected the levels of dry matter, crude protein, and crude fiber in cassava cobs (P <0.01). It was concluded that fermentation of cassava cob with 2% EM-4 together with 5 cc of molasses could increase dry matter content by 0.63%, increase crude protein by 0.95%, and reduce crude fiber by 2.13%. Furthermore, fermentation with bioactivator MA-11 proved more effective in increasing dry matter content, achieving an increase of 2.88%, increasing crude protein to 2.13%, and reducing crude fiber content to 3.71%. Keywords: Bioactivator, Cassava Cobs, EM-4, Fermentation, MA-11.